1993
DOI: 10.1128/jvi.67.3.1638-1646.1993
|View full text |Cite
|
Sign up to set email alerts
|

All three domains of the Epstein-Barr virus-encoded latent membrane protein LMP-1 are required for transformation of rat-1 fibroblasts

Abstract: LMP-1, the Epstein-Barr virus latent membrane protein 1, is the only protein encoded by the virus that has been shown to have the properties of a transforming oncogene in rodent fibroblasts such as Rat-1 cells. LMP-1 is phosphorylated and proteolytically cleaved in Rat-1 cells in a manner similar to that seen in human lymphocytes. In this study, we demonstrate that all three major domains of LMP-1 (N-terminal, transmembrane, and C-terminal domains) are required for the ability to transform Rat-i cells in cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
57
0
2

Year Published

1996
1996
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(60 citation statements)
references
References 18 publications
0
57
0
2
Order By: Relevance
“…Expression of LMP1 in B cells provokes many of the phenotypic changes characteristic of B cell immortalization [29]. LMP1 can also induce cellular changes in cell types other than B cells [30,31]. Although most of the changes induced by EBV infection in the NK cell environment remain to be determined, we demonstrated that induction of IL-2Ra expression by IL-2 is augmented in EBV-infected NK cells.…”
Section: Discussionmentioning
confidence: 68%
“…Expression of LMP1 in B cells provokes many of the phenotypic changes characteristic of B cell immortalization [29]. LMP1 can also induce cellular changes in cell types other than B cells [30,31]. Although most of the changes induced by EBV infection in the NK cell environment remain to be determined, we demonstrated that induction of IL-2Ra expression by IL-2 is augmented in EBV-infected NK cells.…”
Section: Discussionmentioning
confidence: 68%
“…LMP1 acts as an oncogene in established rodent cells (Wang,D. et al, 1985;Baichwal and Sugden, 1988;Moorthy and Thorley-Lawson, 1993) and blocks differentiation in epithelial cells (Dawson et al, 1990;Fahraeus et al, 1990b;Wilson et al, 1990). In Burkitt's lymphoma cell lines LMP1 induces the expression of B cell activation markers CD23 and CD40 and cell adhesion molecules ICAM1, LFA1 and LFA3 and stimulates NF-iB activity (Wang,F.…”
Section: Addition Ebna2mentioning
confidence: 99%
“…Nine viral proteins are expressed in established lymphoblastoid cell lines, five of which appear to be absolutely required for B cell immortalization: EBNA1, 2, 3a, 3c and LMP1 (Hammerschmidt and Sugden, 1989;Cohen et al, 1991;Kaye et al, 1993;Tomkinson et al, 1993;Kilger et al, 1998). Latent membrane protein 1 (LMP1) is the only EBV protein which has a transforming potential in established rodent cell lines (Wang et al, 1985;Baichwal and Sugden, 1988;Moorthy and Thorley-Lawson, 1993). Interestingly, LMP1 induces the expression of the B cell activation markers CD23 and CD40, cell adhesion molecules ICAM1, LAF1 and LFA3 (Wang et al, 1990), and the epithelial growth factor receptor (Miller et al, 1997).…”
Section: Introductionmentioning
confidence: 99%